Monitorización del crecimiento de microorganismos en sistemas cerrados utilizando espectroscopia de impedancia eléctrica - Olguín-S´ánchez, R. A.; Rojas-Rendón., J. A.; Díaz-Campillo., M. J.; Salazar., Y. (Revista Mexicana de Ingenieria Biomedica, 2009)
Nowadays, the supervising of biological process is trying to use the time and production costs optimization. This process involves the microorganism monitoring throughout the biomass growing stages. Therefore, the objective of this study is to obtain the time behavior of the biomass concentrations as function of the impedance changes: both in the magnitude (|Ζ|) and in the phase (Φ). The impendance was monitored by the electrical impedance spectroscopy (eis). To do this, a measurement system was implemented using a lcr impedance-meter and a front-end. The measurement technique uses an eis with four poles. The frequencies used in the system are within the range of 20 hz a 200 khz. Three different culture media were used to perform the monitoring: distilled water, nutrients broth and nutrients broth strengthen with inoculums of the yeast known as saccharomyces cerevissiae. The eis measurements were validated trough the microorganism counting performed in a neubauer chamber. The achieved results shown that the inoculated broth has a change of 2.1% and 0.05° regarding to the ∆|Z| and ∆ Φ respectively in the delay phase. The growing phase has changes of 9.6% and -0.15° in the same variables while the steady state phase showed different values: 1.3% and -0.04°. The death stage was characterized by changes of 3.35% and -0.1° in the same impedance elements. These variations were obtained with respect to the nutrients broth. The time evolution of ∆|Z| and Φ measured with a frequency of 200 khz has a correlation index of 0.95 with respect to the cell’s counting. Therefore, the on-line monitoring of the microorganism concentration using the eis method seems to be a viable method to determine and visualize the different developing stages of cells cultures.